A Study of Adsorption of Zr (IV) on Manganese Dioxide - AI- Taweel, H.H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The adsorption of zirconium, on manganese dioxide from nitric acid solutions has been studied as a function of shaking time, concentration of electrolytes, concentration of adsorbate and temperature effects (25- 90Â°C). Four hours of shaking was appropriate to ensure that the adsorption plateau was reached and the adsorption of zirconium decrease with an increase in nitric acid concentration. The limiting adsorption capacities at 3 molar nitric acid was 0.2 Zr per mole of Mn02. Working at elevated temperature was in favour of the adsorption phenomena.